(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The increasing global shift toward natural and holistic wellness solutions has significantly boosted the demand for Ayurvedic products. Governmental interventions play a crucial role in influencing consumer behavior and enhancing purchase intentions through strategic promotional efforts